Analysis of Implementation of SAK ETAP in Presentation of Financial Reports KSP KOPDIT Tuke Jung Head Office - Emillianus Eo Kutu Goo; Henrikus Herdi; Lidwina Rusmawati (CV ODIS, 2023)
This study aims to determine the application of SAK ETAP to the presentation of the financial statements of KSP Kopdit Tuke Jung Head Office. By analyzing the financial reports, KSP Kopdit Tuke Jung prepared and adjusted them to SAK ETAP. They are collecting data used in this study using interviews and documentation. This type of research uses descriptive qualitative and comparative analysis. The results of this study indicate that the presentation of financial statements at the KSP Kopdit Tuke Jung Head Office consists of comparative balance sheets, comparative shu, notes to the balance sheet financial statements, and notes to the income statement prepared by the KSP Kopdit Tuke Jung Head Office, the presentation is close to the classification of SAK ETAP it just still needs adjustments and a deeper understanding of the presentation and reporting by SAK ETAP.